Last mile energy access for productive energy use in agriculture in Sub-Saharan Africa: What and where is the potential? - Xie, Hua; Ringler, Claudia; You, Liangzhi (2019)
Sub -Saharan Africa has long been beset with food insecurity. Agriculture in the region is predominantly rainfed, which makes the sector highly vulnerable to climate variability. Irrigation is considered as a promising option to boost agricultural production and enhance agricultural resilience. At the same time, Sub-Saharan African countries also suffer from energy poverty. Lack of access to energy services limits the expansion of irrigated agriculture. A joint irrigation-energy planning framework is developed to estimate how much of the economic potential irrigated area could be powered with standalone solar photovoltaic (PV) energy. The modeling framework first compares the costs of motorized irrigation technology under solar and alternative energy solutions (e.g. diesel). The information generated from the comparative analysis informs power source selection in a model that simulates future pathways of irrigation expansion subject to water availability and market opportunities for irrigated crops. We present the joint irrigation-energy planning framework and a first set of results focusing on groundwater-fed irrigation in Sub-Saharan Africa.